Рваные чувства - Колычев Владимир Григорьевич (Любовь зла и коварна, 2016)
Экземпляры: (20190122) / Инвентарный номер: 34544 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 62 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6